Sovereign sukuk in Indonesia : an analysis of the issues from legal and shari'ah perspectives - Armen, Rio Erismen (IIUM Institute of Islamic Banking, International Islamic University Malaysia, 2020)
This study raises issues of Ṣukuk Negara (Indonesian sovereign ṣukuk) issued in Indonesia which are captured from both legal and Sharī'ah perspectives. This is based on perceptions of legal and Shari'ah scholars in Indonesia. By employing a qualitative research approach, this study collects relevant data through library study as well as interviews. The interviews in particular are conducted with selected legal and Shari'ah scholars in Indonesia, in addition to officers of Ministry of Finance of Indonesia which is the main stakeholder for Ṣukuk Negara issuance. Three lists of questions are designed for the interviews. One list is set to collect relevant information from the Ministry of Finance which takes the main role in the issuance of Indonesian sovereign ṣukuk. The second list deals with opinions and ideas of Sharīʿah scholars, and the third list deals with those come from legal expertise background. The interviews are conducted separately with participants, namely: three government officials of the Ministry of Finance, two legal experts, two prominent Shariʿah scholars of Dewan Syariah Nasional - Majlis Ulama Indonesia (DSN-MUI), and one representative of Badan Wakaf Indonesia (BWI) in connection to waqf investment in Ṣukuk Negara. The findings are composed into three parts. The first part deals with the concept of Indonesian sovereign ṣukuk in terms of definition, main elements in issuance, as well as structures designed and developed by the Government of Indonesia as issuer. The second part deals with legal framework of Ṣukuk Negara and legal issues that focus on four main issues, namely: (i) legal conundrum in embracing of the Beneficial Right concept, (ii) legal issues on SPV & Trustee of Ṣukuk Negara, (iii) legal arrangement for Sharīʿah governance of Ṣukuk Negara, and (iv) legal protection for investment in Ṣukuk Negara Instrument. The study acknowledges that the adoption of Beneficial Right concept as well as SPV and Trustee authorized by Ṣukuk Negara Law 2008 needs to be further perfected. Also, the study finds that the mechanism of legal resolve for the default case of Ṣukuk Negara needs to be ruled in Ṣukuk Negara Law 2008. The third part especially deals with Shariʿah framework of Ṣukuk Negara and Sharīʿah issues that are condensed into three main issues, namely: (i) discussion on Beneficial Right from Sharīʿah perspective, (ii) Sharīʿah debate on Ṣukuk Negara structure, and (iii) prospect for developing the Ṣukuk Negara structure. The study concludes that the structure of Ṣukuk Negara contains a problem in term of similarity with doubtful contract models in Islamic jurisprudence such as Bayʿ al-Wafa’, Bayʿ al-Istiglal, al-ʿAqd al-Ṣuriy, that involve al-Heyal (legal ruses) debated by Sharīʿah scholars. In addition, the study also suggests the stakeholders to explore and design other new structures for Ṣukuk Negara.